EXPLORING THE PHILOSOPHICAL CONCEPT OF EMERSON’S “THE OVER SOUL” IN HIS ESSAYS - Albertin Minderop (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
The objective of this research is to demonstrate the deepest meaning of the philosophical concept of "The Over-Soul" by Ralph Waldo Emerson (1803-1882) found in some of his essays which were considered to be too difficult to decipher as there are many symbols and metaphors. This paper discussesBhagavad Gita and Sufism teaching as those religious epics influence Emerson’s work; in addition, the hermeneutical method of Paul Ricouer as one philosophical approach is used to interpret symbols and metaphors in his essays. The result of the study concludes that “The Over Soul” or the “divine light” is able to provide thefeeling of “Perfect Happiness” and became “the Whole-Man” by performing the following: having retrospect, doing introspection, contemplation and meditation in order to reinforce self-control attitude